Differential membrane curvature induced by distinct protein conformers - Malshikare, Hrushikesh; Prakash, Shikha; Sengupta, Durba (Soft Matter, 2023)
Membrane topology changes are associated with various cellular processes and are modulated by synergistic effects between lipid composition and membrane-associated proteins. However, how protein shape or conformational dynamics couples to membrane molecular properties remains unclear. In this work, we aim to investigate this coupling behavior using the curvature-inducing protein caveolin-1. We considered distinct protein conformers of the helical hairpin protein corresponding to different protein shapes, such as the wedge and the banana-shaped conformers. The different protein conformers were simulated in a coarse-grain representation in the presence of cholesterol-sphingomyelin rich membrane. We observed that membrane curvature is dependent on protein shape and is the lowest for the wedge conformer and maximal for the banana conformer. The differences in the net stress between the two membrane leaflets, calculated from the lateral pressure profile distributions in lipid bilayers for different protein conformers, show a similar trend. In conjunction, we show that cholesterol and sphingomyelin clustering in the membrane is modulated by protein shape. Overall, our results provide molecular-level insights into the coupling between membrane topology, protein shape and lipid clustering in cell membranes.